Photonics: Photodiodes and Metamaterials for Thermophotovoltaics and Photodetection Applications. - Shemelya, Corey. (2017)
Abstract: Photonics is the study of the propagation and interaction of light and matter. This research aims to utilize the general field of photonics to optimize multiple stages of a thermophotovoltaic energy generator as well as create a dynamic polarization sensitive surface for use in photodetection technologies. To accomplish these sizable goals multiple types of photonic structures and devices have been studied and characterized including high-temperature metamaterial emitters, 2-dimensional photonic crystal filters, dynamic metamaterial polarization-filters, and interfacial miss-fit array photodiodes. The goal of this research is to provide a series of cutting edge building blocks which could be integrated together in a variety of different applications. The results of this work have potential applications ranging from photodetection, to photonic filtering, to renewable energy generation.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Electrical Engineering.; Advisor: Thomas Vandervelde.; Committee: Aleksandar Stanković, Marc Hodes, and Ganesh Balakrishnan.; Keywords: Electrical engineering, Optics, and Materials Science.